ANALISIS KRITERIA INVESTASI PADA CV. ILMI DI KOTA MAKASSAR - Aisyah Aisyah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
Results of the implementation for four years (2011-2014) , business / project run by CV Ilmi eligible to run . It is based on the assessment of the investment criteria of net present value (NPV) and internal rate of return (IRR) . Furthermore, NPV = Rp . 7,815,595.00 which means positive cash flow or the present value of Rp . 1,451,655,095.00 greater than the original investment (OI) amounted Rp.1.443.839.500,00 While IRR = 13:22 % meaning greater than the interest rate on financial institutions in the amount of 12 % That projects run by CV . Ilmi for four years (2011-2014) based on the assessment criteria , namely investment payback period method . From the analysis of the results obtained payback period PP = 3:11 years or 3 years and 1 month means that the payback period of the invested capital more quickly than the age specified investment is 4 years